Komparasi dan Determinan Pembangunan Sumber Daya Manusia antara Kabupaten Kota di Sumatera Barat - Fadli, Khairul; Aimon, Hasdi (Universitas Negeri Padang, 2023)
This study aims to analyze the comparison and determinants of human development between cities and districts in the Sumatera Barat. The source of the data was taken from the Indonesian Central Statistics Agency. This study used panel data with the time series data from 2010–2021 and the cross-section between cities and districts in Sumatera Barat. This study utilizes the Random Effect Model (REM) panel data regression analysis model to infer the determinant of human development. The results show that human development in the city is higher than in the district, with an average of 76.4 compared to the district with an average of 66.8. Economic growth is the main determinant of human development for both the city dan districts. Economic growth also has a positive and significant impact on human development in districts and cities. Furthermore, the population, the poor population, and the unemployment rate have no significant effect on human development. Based on this research findings, suggests the government of Sumatera Barat promotes a pro-poor and pro-employment growth strategy. The economic development in Sumatera Barat should also be more equitable between cities and districts.